Audit Delay and Risk Management Disclosure in Capital Market: Some Nexus Considerations - Bulutoding, Lince (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
The reluctance of modern firms to disclose their risk management is often investigated; however, how it interacts with audit delay is still underrepresented in academic investigations. This article thus provides a glimpse of how profitability and leverage serve as predictors of audit delay and the risk management disclosure in Indonesia-listed firms, aside from managerial ownership as the moderating variable. A five-year market movement becomes the investigated data in a quantitative approach. The findings reveal that profitability and leverage are not related to risk management disclosure, but they affect audit delay and subsequently to the disclosure. Managerial ownership also boosts the relationships of the dependent variables. No Indirect relationships are reported.